DETERMINAN KINERJA KEUANGAN DAN DAMPAK MODERASI STRATEGI BERSAING - Riris Rotua Sitorus; Wimbildon Sihotang (Universitas 17 Agustus 1945 Jakarta, 2017)
This study was conducted to examine the effect of promotional costs and debt policy on financial performance with competitive strategy as moderating. Research was conducted on property and real estate companies listed on the Indonesian Stock Exchange. The independent variables of this research are the cost of sale by proxy log promotional costs and debt policy with proxy Debt To Equity Ratio (DER). The dependent variable of this research is financial performance calculated using Return On Equity (ROE) with a competitive strategy as moderating using proxies are cost leadership was measured by Utiliziation Asset Efficiency (AUE) and differentiation was measured using the Premium Price Capability (PPC). The samples used were 29 properties and real estate companies listed on the stock exchange during the period 2011-2015 and generate profits. This study was conducted descriptive and use multiple regression. The research proved that the fee did not significantly affect the Promotion of Financial Performance. Debt policy significantly affected financial performance. Moderation Cost Leadership Competitive Strategy and Competitive Differentiation Strategy significantly affected financial performance. Cost Leadership Competitive Strategy and Competitive Differentiation Strategy can not amplify the effect of the fee on the Promotion of Financial Performance. Competitive Cost Leadership strategy, were not able to moderate the influence of Debt Policy on Financial Performance. Differentiation Competitive Strategy was able to moderate the influence of Debt Policy on Financial Performance.